COMMUNICATIVE ACTS AND PHONOLOGICAL PROCESSES OF MALE CHILDREN AT FREE PLAY - Fuji Faye Dianne Pastor; Rowanne Marie Maxilom -Mangompit (Kajian Linguistik dan Sastra, 2020)
This study was conducted to explain the communicative acts and phonologicalprocesses of Cebuano-English speaking children in interacting with their parent duringfree play, using video-tape recorder. It is a qualitative and quantitative method of the 4 male Cebuano- English speaking children aged 4 years old residing in Palompon, Leyte. The research result showed that the most occurring communicative acts were obliging andcontrol acts. Also the most dominant phonological processes of children were stopping,consonant cluster reduction, and gliding.Keywords: communicative acts, phonological processes, play